Extração de óleos essenciais da espécie vegetal (menta e camomila) com etanol e clarificação do extrato obtido com zeólita tipo Ca-X - Santos, Cátia (2008)
In spite of the Brazilian flora wealth with about 55 thousand species and of wide use of medicinal plants by the population, there is consent about the inadequacy of scientific studies on phytoterapy applications. Chamomile (Matricaria recutita [L Rauschert]) and mint (Mentha arvensis) are two of the plants selected by the Parana`s Health ClerkshipPhytotherapy Project - SUDS, among 21 species, for medicinal use in the public health network. This justifies the study of the ethanol's extractions to obtain the extracts (oil + ethanol + pigments). For the essential oil's extractions from chamomile used the best (5g chamomile/30mL de EtOH), to according others works, with regard to the yield and composition of them. The aim of this work was to study the oil's extractions essential of the chamomile and clarification from mint and chamomile, by using zeolites Ca-X, as well as to identify the principals compounds obtained from extraction with ethanol was submitted at adsorption inside of bed with zeolites Ca-X and verified that the zeolites Ca-X absorbed almost all natural pigments from mint, producing a brightly essential oil. The amount of pigment absorbed by zeolites Ca-X was determined by UV-Vis spectroscopy at 665 nm and the extract chemical was evaluated by gas chromatography mass spectrometry.